Genome‐wide analysis of colorectal cancer based on gene‐based somatic copy number alterations during neoplastic progression within the same tumor - Shun Yamada; Mitsumasa Osakabe; Noriyuki Uesugi; Naoki Yanagawa; Takayuki Matsumoto; Hiromu Suzuki; Tamotsu Sugai (Cancer Medicine, 2023)
Abstract Background The objective of this study was to elucidate the association between neoplastic progression and somatic copy number alterations (SCNAs) occurring within the same colorectal cancer (CRC) tumor. Methods We investigated SCNAs to identify the progression from a high‐grade intramucosal lesion (HGIL) to an invasive front lesion (IFL), via an invasive submucosal lesion (ISL), within the same tumor using a crypt isolation method combined with a SNP array. Immunohistochemistry was also performed. Results We identified 51 amplified genes that potentially promote progression from HGIL to ISL and 6 amplified genes involved in the progression from ISL to IFL. Of the 51 genes involved in HGIL to ISL progression, TORC1, MSLN, and STUB1, which are closely associated with CRC, were identified as candidate markers of submucosal invasion. However, no candidate genes were identified among the six genes associated with ISL to IFL progression. In addition, the number of total SCNAs and the number of gains were correlated with cancer progression (from HGIL to IFL). Finally, immunohistochemistry revealed higher expression of TORC1, MSLN, and STUB1 in ISL than in HGIL. Conclusions These results suggest that specific SCNAs are required for acquisition of invasive ability in CRC, and the affected genes are potential markers of invasion.